A bench-stable low-molecular-weight vinyl azide surrogate for a cascade reaction: facile access to novel N-vinyl-1, 2, 3-triazoles. Issue 18 (7th August 2020) - Liu, Zhenhua; Wang, Lianxiao; Yu, Tian; Sun, Yanan; Chen, Huimin; Gao, Wen; Tang, Bo
Abstract : A novel metal-catalyzed cascade reaction of stable low-molecular-weight vinyl azide surrogate with S-/O-nucleophiles and alkynes was disclosed in a general fashion, thus providing mild and efficient access to various N -vinyl-1, 2, 3-triazoles bearing new functional groups. Abstract : A novel metal-catalyzed cascade reaction of a stable low-molecular-weight vinyl azide surrogate bearing a β-oxygen substituent in a general fashion was disclosed. The orderly insertion of S-/O-nucleophiles and alkynes, for the first time, successfully afforded a diverse range of sulfuryl-substituted N -vinyl-1, 2, 3-triazoles in good yields.